2016
DOI: 10.1186/s12885-016-2817-9
|View full text |Cite
|
Sign up to set email alerts
|

Time trend analysis of primary liver cancer incidence in Sihui county of Guangdong Province, China (1987–2011)

Abstract: BackgroundSouthern China is an endemic area for primary liver cancer (PLC), but it is unclear if rates have changed in recent decades. We evaluated PLC incidence and estimated the effects of age, period of diagnosis, and birth cohort in Sihui City, Guangdong Province, China.MethodsAge-standardized rates (ASRs) of PLC were examined for both males and females from 1987 to 2011. Joinpoint regression analysis was conducted to estimate the annual percent changes in PLC incidence. The age-period-cohort (APC) model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…PLC incidence and its temporal trends are heterogeneous by sex and age . Males were deemed to have a 2‐ to 3‐fold higher risk than females for developing PLC, and the incidence trends for the 2 sexes are for the most part not in alignment . The average age at diagnosis of PLC is approximately 60 years .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLC incidence and its temporal trends are heterogeneous by sex and age . Males were deemed to have a 2‐ to 3‐fold higher risk than females for developing PLC, and the incidence trends for the 2 sexes are for the most part not in alignment . The average age at diagnosis of PLC is approximately 60 years .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Males were deemed to have a 2-to 3-fold higher risk than females for developing PLC, and the incidence trends for the 2 sexes are for the most part not in alignment. 11,12 The average age at diagnosis of PLC is approximately 60 years. 13,14 However, PLC among middle-aged people (age 30-59 years) and even younger populations (age <30 years) is not rare, which causes a heavier disease burden than that of PLC in older patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no data on the epidemiology of HCC in mainland China, while these have been widely reported in the United States, Australia, Denmark, Thailand and many other counties and areas [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Only a few studies have reported the incidence and mortality rates of primary liver cancer in some regions of China, including Shanghai, Guangzhou, Shenzhen, Chongqing, Fuzhou, Nantong, Sihui and other cities [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. However, almost all of the cities mentioned above are located in the south of China; the changes in prevalence, incidence, and mortality of primary liver cancer have not yet been examined in Northern China, and much less for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that PLC was the third most common type of cancer in Guangzhou, with a WASIR of 20.96/100 000 being observed during the period of 2004-2013, which was substantially higher than the global (12.49/100 000) 1 and the national averages (19.28/100 000), 12 and considerably lower than in Sihui (30.80/100 000) 13 and Qidong (41.37/100 000). 14 major risk factor of liver cancer, showed a trend similar to that of liver cancer incidence in males, and could lead to a remarkable difference by sex.…”
Section: Discussionmentioning
confidence: 47%